PENGELOLAAN LAYANAN PEMBELAJARAN ANAK JALANAN DI LEMBAGA PPAP SEROJA SURAKARTA - Rochimah, Nur Aprilia (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2016)
The purpose of research to describe the learning plan of street children in Seroja PPAP Institute Surakarta, describe the lesson in Surakarta Seroja PPAP Institute, describes the evaluation and follow-up study of Street Children in Institutions PPAP Lotus Surakarta. This study uses descriptive qualitative case study research design. The data used primary and secondary data. Data source informant, events or activities with resource informant. Data collection techniques with interview, observation, and document analysis. The validity of the data with data triangulation technique, triangulation methods and reviews informant. Analysis of data using data analysis interactive model of data collection, data reduction, data display and conclusion. Based on these results it can be concluded that the Planning Institute of Education for Street Children in Surakarta using Seroja PPAP Curriculum SBC 2006, do not use the syllabus and do not write lesson plans. The lesson begins with a prayer. Learning methods used mentoring, modeling, lectures, private and project base learning. Media and learning resources are used in the form of books diktat, LKS and white boards. Activities cover, ended by giving homework. Attitudes and skills assessment carried out by observation. Evaluation of learning has not been successful because the value has not reached the standard KKM. Follow-up for the provision of remedial, then to the attitude with mentoring and counseling.